Staphylococcus aureus Hemolysins, bi-component Leukocidins, and Cytolytic Peptides: A Redundant Arsenal of Membrane-Damaging Virulence Factors? - Vandenesch, Francois; Lina, Gérard; Henry, Thomas (Frontiers in Cellular and Infection Microbiology, 2012)
One key aspect of S. aureus virulence lies in its ability to target the host cell membrane with a large number of membrane-damaging toxins and peptides. In this review, we describe the hemolysins, the bi-component leukocidins, which include the Panton Valentine Leukocidin, LukAB/GH, LukED and the cytolytic peptides (Phenol Soluble Modulins). While at first glance, all these factors might appear redundant, it is now clear that some of these factors play specific roles in certain S. aureus life stages and diseases or target specific cell types or species. Here, we present an update of the literature on toxins receptors and their cell type and species specificities. Furthermore, we review epidemiological studies and animal models illustrating a role of these membrane-damaging factors in various diseases. Finally, we emphasize the interplay of these factors with the host immune system and highlight all their non-lytic functions.